A New Genus of Chiggers (Trombidiformes: Trombiculidae) from Bats in Jamaica - Bassini-Silva, Ricardo (2021)
Background: The Caribbean country Jamaica has only seven reported chigger species. Of these, one was recorded from bats. Methods: For the specimens examined in this study were provided drawings, measurements, and microscopy images on a Microscope Zeiss. This material is deposited in the Smithsonian National Chigger Collection. Results: In the present study, we describe a new genus and species parasitizing the Antillean ghost-faced bat in Jamaica. This new genus can be separated from all other genera of this family for the following combination of features: (1) palptarsus with four branched and three nude setae; (2) 3-pronged odontus; (3) femur I divided into basifemur and telofemur; and (4) 3 σ on genu I. Conclusion: The description of this new genus contributes to the increase in the knowledge of chiggers that parasites bats in Jamaica. Also, this is only the second record of a chigger parasitizing this host in this country.